Influence of hypohydration on intermittent sprint performance in the heat - Maxwell, N. S.; Mackenzie, R. W. A.; Bishop, D. (International Journal of Sports Physiology and Performance, 2009)
Purpose: To examine the effect of hypohydration on physiological strain and intermittent sprint exercise performance in the heat (35.5 ± 0.6°C, 48.7 ± 3.4% relative humidity). Methods: Eight unacclimatized males (age 23.4 ± 6.2 y, height 1.78 ± 0.04 m, mass 76.8 ± 7.7 kg) undertook three trials, each over two days. On day 1, subjects performed 90 min of exercise/heat-induced dehydration on a cycle ergometer, before following one of three rehydration strategies. On day 2, subjects completed a 36-min cycling intermittent sprint test (IST) with a -0.62 ± 0.74% (euhydrated, EUH), -1.81 (0.99)% (hypohydrated1, HYPO1), or -3.88 ± 0.89% (hypohydrated2, HYPO2) body mass deficit. Results: No difference was observed in average total work (EUH, 3790 ± 556 kJ; HYPO1, 3785 ± 628 kJ; HYPO2, 3647 ± 339 kJ, P = 0.418), or average peak power (EUH, 1315 ± 129 W; HYPO1, 1304 ± 175 W; HYPO2, 1282 ± 128 W, P = 0.356) between conditions on day 2. Total work and peak power output in the sprint immediately following an intense repeated sprint bout during the IST were lower in the HYPO2 condition. Physiological strain index was greater in the HYPO2 vs. the EUH condition, but without changes in metabolic markers. Conclusion: A greater physiological strain was observed with the greatest degree of hypohydration; however, sprint performance only diminished in the most hypohydrated state near the end of the IST, following an intense bout of repeating sprinting.